How breastfeeding behavior develops in women with gestational diabetes mellitus: A qualitative study based on health belief model in China - Qian, Pan; Duan, Lixia; Lin, Rujiao; Du, Xiwang; Wang, Dan; Liu, Chenxi; Zeng, Tieying (Frontiers in Endocrinology, 2022)
Abstract Background Gestational diabetes mellitus (GDM) is a disease that women develop hyperglycemia during pregnancy, which was associated with long-term health burden for both mother and their offspring, such as future type 2 diabetes mellitus (T2DM). Although breastfeeding was expected to mitigate metabolic sequelae for both mothers and their newborns, the prevalence of breastfeeding in GDM mothers are sub-optimal worldwide. Objective To explore the experience of GDM women of the disease and how they develop their feeding behaviors. Methods This study was conducted in three branches of an integrated tertiary hospital in the central area of China. Mothers who were diagnosed with GDM without other complications and give birth no more than 6 months were approached based on a purposive sampling. GDM mothers’ experience of the disease and breastfeeding were collected via in-depth interview. A theory-driven thematic analysis based on Health Belief Model (HBM) were applied for data analysis. Results 16 GDM mothers were included in the current study, with nine used breastfeeding, six used mixed feeding and one used artificial feeding, respectively. Nine themes were identified, including: GDM diagnosis and severity, information searching and GDM knowledge, GDM management, perceived susceptibility of future diabetes, perceived severity of future diabetes, perceived benefits of breastfeeding, perceived barriers of breastfeeding, decision making process of feeding and social support. Generally, mothers with GDM lack reliable sources of information, considered the disease as a minor, transient illness during pregnancy, and failed to realize the long-term risk of GDM and the protective effect of breastfeeding to themselves and their babies. They rarely considered GDM in their feeding decision. Instead, the formation of feeding behaviors depends on the balance between benefit and barriers of breastfeeding and the level of social support. Conclusion To promote breastfeeding, a multi-facet intervention targeted on HCPs, GDM mothers and their networks were important to help GDM mothers form a correct understanding of the disease and breastfeeding, and increase their capacity of breastfeeding.